MALL IN LEARNING ENGLISH GRAMMAR FOR HIGHER EDUCATION STUDENTS - Nur Rosita; Nora Fudhla; Bayu Hadi Saputro (Fakultas Bahasa dan Seni UNP, 2019)
The 21stcentury learning trend with mobile devices has made significant impacts on the educational setting. It promotes students’ autonomous learning attitude to have their own learning setting anytime, anywhere, and in any way as the purpose of lifelong learning. It is also applied to build students’ 21stcentury skills known as 4-Cs; collaboration, communication, critical thinking, and creativity as well as digital literacy. On the other hand, there are some questions and concerns being echoed around the matter of balancing pedagogy and technology on the grammar learning content for university level students. This article is a part of developmental research that focuses on an analysis of the principles and features of mobile technology support tools for learning English grammar in higher education. A questionnaire using online Google form is administered to the 79 students to see their perspective on learning grammar in 21stcentury mode. Further, the data are gathered in qualitative-descriptive method to find the appropriate criteria. This study meets a basic model preference to build a MALL-Based educational app that can support English grammar learning in Universitas Negeri Padang. It can be concluded that the MALL for grammar should cover all teaching-learning elements like sources and assessments.